Evaluation of two extenders for cryopreservation of semen from golden-headed lion tamarin (Leontopithecus chrysomelas) - Arakaki, Paloma Rocha (2017)
Many Neotropical primate species are endangered of extinction. Reproductive biotechnologies can consistently contribute to species conservation, being among them the genetic resource banks. However, success in the use of such technologies relies on advances in the knowledge of basic reproductive biology of a given species. During these processes, assessment of sperm quality is of supreme importance. We focused our work in captive golden-headed lion tamarins (Leontopithecus chrysomelas), housed at São Paulo Zoological Park Foundation. Leontopithecus sp. is a very important target for the development of reproductive techniques aiming conservation, as all species from this genus are classified as endangered or critically endangered of extinction by IUCN. For the evaluation of sperm quality in L. chrysomelas, techniques like sperm-binding assay, and the non-fluorescent staining for evaluation of acrosome integrity fast-green/rose-bengal, plasma membrane integrity eosin-nigrosin and mitochondrial activity 3.3 diaminobenzidine were validated for fresh semen. We have also validated an acrosome integrity evaluation technique coomassie blue staining, for thawed samples due to the inadequacy of the method used for fresh semen. Some Neotropical primates species show variation in semen quality over the year. In order to assess semen quality for this species and to verify if golden-headed lion tamarin presents this variation, we collected semen in dry and rainy seasons, during different periods of breeding season in the interval of conceptive periods and in the end of the second conceptive period. Testicular measurements were taken prior each semen collection, and a significant difference was found in total testicular volume between seasons, with major volumes found during dry season (p = 0.0011). Samples collected during rainy season showed higher percentage of total motility (x = 93.85) and intact plasma membrane (x = 95.54) (p = 0.0149 and p = 0.0279, respectively), in comparison with dry season (total motility x = 90.96 and intact plasma membrane x = 92.46). Even with those differences, semen from both seasons presented good quality. The success rate for collection with penile vibrostimulation technique was of 100%, and all samples obtained were constituted by only a coagulated fraction. Despite not achieving coagulum dissolution, we were able to access a high number of spermatozoa by adding Biggers-Whitten-Whittingham (BWW) medium to the coagulum for 30 min at 37°C, and performed all proposed analyzes. The same samples used of fresh analyzes were subsequently submitted to cryopreservation using two different commercial extenders BotuBOV® (BB) and Freezing Medium with Glycerol and Gentamicin Test Yolk Buffer® (TYB). Thawed semen samples were analyzed with the same methods previously validated and were also evaluated for the susceptibility to oxidative stress through quantification of induced thiobartituric acid reactive substances (TBARS). For all seminal parameters assessed, no significant difference was observed between BB and TYB, except that BB presented a higher percentage of intact acrosome (p = 0.0101) and concentration of TBARS (p = 0.0005). Despite those differences, thawed semen from both extenders performed similarly at spermegg binding assay. From our work, we observed that the proposed methods were successfully validated for L. chrysomelas. Fresh semen quality was very high and both extenders were successful in cryopreserving semen.